Site-directed mutagenesis of n-terminal Alpha Helix of J15 lipase - Lee, Mei Ying (2015)
The intrinsic propensity of each amino acid residue forming α-helices in a protein determines the stability of a protein. The purpose of this study is to improve the stability of the protein by stabilizing the N-terminal α-helix. Therefore, mutations were focused on N-terminal helix of J15 lipase derived from Photobacterium sp. strain J15. The structure of J15 lipase was modeled based on M37 lipase crystal structure as a template. Asp6 of N-terminal helix was chosen as competition of Asp6 with the adjoining main chain hydrogen bonding interaction could destabilize the N-terminal helical structure. In silico analysis using SDM and I-mutant 2.0 revealed that D6L and D6I enhanced the stability of mutated J15 lipases with G of 5.12 kcal/mol and 0.82 kcal/mol respectively. In order to validate the in-silico prediction, the gene encoding J15 lipase was cloned into pEasy-E2 expression vector and transformed into Escherichia coli BL21(De3). Point mutation was generated using Fast Mutagenesis System to increase the mutation efficiency. The Aspartate residue at the sixth position of the N-terminal α-helix was substituted with Isoleucine and Leucine. The wild-type and mutants were induced with 0.015 mM IPTG at 30°C for 16 h. The expected size of the protein was approximately 40.11kDa. Both the wild-type and mutants showed low expression level and most of the proteins were present as insoluble bodies. The specific activity of the crude protein calculated for J15 lipase is 1.953 U/mg, D6I is 1.55 U/mg and D6L is 1.429 U/mg. Overall, the specific activity was low. Due to time constraint, further experimental work could not be performed on time and it was not able to validate the result with the in-silico protein stability predictions.